Neurolinguistic Programming (NLP) In the Teaching Process (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses the possibility of applying neuro-linguistic programming (NLP) to teaching English.Neurolinguistic programming is one of the most superb areas of cutting-edge psychology. It provides psychological competencies for appreciation human beings and enhancing communication. The most essential thoughts and strategies of NLP are extensively used in a variety of fields. This helps to enhance them and make them extra successful. NLP stands for Neuro-Linguistic Programming. These are neurology, linguistics (transformational grammar) and cybernetics (systems theory). The suggested methods and tactics are provided, together with their benefits and drawbacks. Learning a foreign language is a challenging and complex skill, thus breaking it up into several related abilities is necessary to model it. With the use of NLP tools, you might discover several fascinating details that are often obscured to English language teachers. They include eye motions, behavioral patterns, underlying assumptions, tactics, nonverbal replies, anchor actions, and more. It’s possible to simulate language learning